A Reliable and Precise Protocol for Urea Quantification in Photo/Electrocatalysis. Issue 9 (5th July 2022) - Li, Dong; Xu, Ning; Zhao, Yunxuan; Zhou, Chao; Zhang, Li‐Ping; Wu, Li‐Zhu; Zhang, Tierui
Abstract: To comply with the trend toward green and sustainable development of the fine chemical industry, multitudinous promising technologies (e.g., photocatalysis and electrocatalysis) are beginning to dabble in the green synthesis of fine chemicals, particularly urea synthesis. Whilst numerous advances are made in mechanistic understanding, the low yield reported so far also imposes more stringent requirements on the reliability and anti‐interference of the detection method. Herein, the applicability of frequently used methods for urea quantification is methodically compared. In terms of the experimental results, a precise and methodical protocol for urea quantification or evaluation in photo/electrocatalysis is explored and established, with emphasis on screening quantitative methods under specific conditions and indispensable isotopic tracing experiments. The budding urea photo/electrosynthesis urgently demands a rigorous protocol, including the rapid isotopic identification and evaluation criteria, capable of promoting healthy development in the future. Abstract : A precise and methodical protocol for urea quantification or evaluation in photo/electrocatalysis is explored and established after thorough investigation and exploration of the superiorities and limitations of the frequently used urea quantitative methods in emerging photo/electrocatalytic urea synthesis, with emphasis on the screening quantitative methods under specific conditions and indispensable isotopic tracing experiments.